2001
DOI: 10.1074/jbc.m103013200
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Targeting Domains of γ and δ Calmodulin-dependent Protein Kinase II

Abstract: Ca2؉ /calmodulin-dependent protein kinase II (CaMK-II) isozyme variability is the result of alternative usage of variable domain sequences. Isozyme expression is cell type-specific to transduce the appropriate Ca 2؉ signals. We have determined the subcellular targeting domain of ␦ E CaMK-II, an isozyme that induces neurite outgrowth, and of a structurally similar isozyme, ␥ C CaMK-II, which does not induce neurite outgrowth. ␦ E CaMK-II co-localizes with filamentous actin in the perinuclear region and in cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 40 publications
6
43
0
Order By: Relevance
“…A highly selective cell-permeable peptide inhibitor of CaMKII [antCNt (Chang et al, 1998;Fink et al, 2003)] and downregulation of ␤-CaMKII with siRNA reduced movement of neuritic branches and decreased arborization. An ␣/␤-CaMKII chimera with partial actin binding produces a partial effect on the size of the dendritic arbor (Fink et al, 2003), and non-neuronal isoforms with partial actin binding produced actin-rich neurite extensions (Caran et al, 2001). The findings are consistent with a need for actin localization for the kinase to affect neurite activity.…”
Section: Cytoskeletal Targetingsupporting
confidence: 77%
“…A highly selective cell-permeable peptide inhibitor of CaMKII [antCNt (Chang et al, 1998;Fink et al, 2003)] and downregulation of ␤-CaMKII with siRNA reduced movement of neuritic branches and decreased arborization. An ␣/␤-CaMKII chimera with partial actin binding produces a partial effect on the size of the dendritic arbor (Fink et al, 2003), and non-neuronal isoforms with partial actin binding produced actin-rich neurite extensions (Caran et al, 2001). The findings are consistent with a need for actin localization for the kinase to affect neurite activity.…”
Section: Cytoskeletal Targetingsupporting
confidence: 77%
“…To date, there are 13 recognized CaMKIIγ splice variants. Similarly, 15 splice variants have been identified for the δ gene [29]. Both CaMKIIγ and CaMKIIδ are ubiquitously expressed with the highest levels observed in peripheral tissue [134].…”
Section: Decrease Of Camkiiγ and Increase Of Camk Iiδmentioning
confidence: 99%
“…Separate studies identified a cytosolic targeting domain in specific ␥ and ␦ isoforms (6). Because CaMKII is expressed as large homo-and heteromultimeric holoenzymes, the subunit composition may confer subcellular targeting and specific protein interactions directing enzymatic activity to specific cellular compartments and functions (4,6,43).…”
mentioning
confidence: 99%